Stigma in Mental Illness: Relative’s Perspective - Adhikari, S R (Journal of Psychiatrists' Association of Nepal, 2015)
Introduction: Stigma is an important determinant in mental illness, which determines awareness, symptom recognition and treatment adherence. It is an important factor due to which relatives of patients with psychiatric disorders decide treatment and further evaluation. Materials and Methods: This is cross-sectional retrospective study done at medical college. Valid and standardized rating scales along with socio-demographic profile were used to assess perception, awareness and attitude regarding stigma against mental illness among relatives of patients who have mental illness.Results: Most family members did not perceive themselves as being avoided by others because of their relative’s hospitalization, half reported concealing the hospitalization at least to some degree. Both the characteristics of the mental illness (the stigmatizing mark) and the social characteristics of the family were significantly related to levels of family stigma. Care givers whose relative had experienced an episode of illness within the past 6 months reported greater avoidance by others. Conclusion: Stigma experienced by relatives is pervasive and everlasting. It deeply affects emotional, social and occupational aspects of care giver also which leads to concealment of their patient’s illness, which have long term detrimental situations and non-compliance of medications.J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 37-42DOI: http://dx.doi.org/10.3126/jpan.v3i2.12393